PERILAKU PERAWAT DALAM PENERAPAN PENCEGAHAN DAN PENGENDALIAN INFEKSI NOSOKOMIAL DI RAWAT INAP RS TK.II 14.05.01 PELAMONIA MAKASSAR - Hastuti Tuti; Mohammad Ardani Samad; Ali Imran; Sriyani Windarti; Mangindara Mangindara (LPPM Universitas Awal Bros, 2026)
Nosocomial infections are still a health problem in both developed and developing countries. Health care-acquired infections are a major cause of death and increased morbidity among hospitalized patients. Hospitalized patients can facilitate transmission to hospitalized patients. The aim of the research is to determine the behavior of nurses in implementing the prevention and control of nosocomial infections in inpatients at TK.II Hospital 14.05.01 Pelamonia Makassar. This research method is quantitative research with a cross sectional study approach. This research was carried out with a sample of 192 nurses who were determined using a total sampling technique for collecting data in this research through distributing questionnaires with Univariate and Bivariate analysis techniques with the SPSS program with the Chi-square test. Research Results and Conclusions The results of the study using the chi-square test showed that the variables were family (p=0.001), facilities (p=0.031), motivation (p=0.002) and physical environment (p=0.031), peers (p=0.000) , which means there is a significant relationship between family, facilities, motivation, physical environment and peers and nurses' behavior in implementing the prevention and control of nosocomial infections at TK.II Hospital 14.05.01 Pelamonia Makassar. TK.II Hospital 14.05.01 Pelamonia Makassar suggests that the hospital should provide training to nurses about nosocomial infections and create special programs to prevent the occurrence of nosocomial infections and assign appropriate tasks to nurses. with the competencies they have